(untitled) (London, 1973)
Tells us the political economy of technical advance in underdeveloped countries
Keywords: Science,Khoa học,Technology,Công nghệ; Social aspects,Khía cạnh xã hội,Social aspects,Khía cạnh xã hội; Developing countries,Quốc gia đang phát triển,Developing countries,Quốc gia đang phát triển